Trends and Variations in the Use of Inhaled Nitric Oxide in Preterm Infants in Canadian Neonatal Intensive Care Units - Soraisham, Amuchou S.; Harabor, Andrei; Shivananda, Sandesh; Alvaro, Ruben; Ye, Xiang Y.; Lee, Shoo K.; Shah, Prakesh S.; on behalf of the Canadian Neonatal Network (American Journal of Perinatology, 2016)
Objective To determine the proportion of infants who receive inhaled nitric oxide (iNO), and to characterize the variations in its use by gestational age (GA) and center in infants <34 weeks' gestation.Design Retrospective analysis was performed in infants born at <34 weeks' gestation and admitted to neonatal intensive care units participating in the Canadian Neonatal Network between January 2010 and December 2013.Results Of 19,525 infants, 831 (4.2%) received iNO. A total of 369 infants (44%) received iNO during the first 2 days after birth. The proportion of neonates who received iNO in the 22 to 25, 26 to 29, and 30 to 33 weeks' GA groups was 16.1, 6.0, and 1.3%, respectively. Infants in whom iNO was initiated in the first 2 days of age received it for a shorter duration (median, 3 days; interquartile range [IQR], 2–5) as compared with those who started after 2 days (median, 5 days; IQR, 2–11). The use of iNO varied by center, ranging from 0 to 15.5% (p < 0.001).Conclusion Out of every 25 infants born at <34 weeks' gestation in Canada received iNO, with the highest rate of use in infants born at lower gestation. Further research to identify reasoning, efficacy, and safety of iNO in preterm infants is warranted.
Keywords: infant; inhaled nitric oxide; neonatal intensive care unit; practice variation; preterm